Effectivity of Using Growth Retardants on Shorea assamica Dyer Seedling at Nursery - Irawan, Arif; Iwanuddin, Iwanuddin (Balai Penelitian Kehutanan Manado, 2015)
The use of growth retardants widely used as a solution in the storage material for the propagation of plant species that have recalcitrant seed types. White meranti (S.assamica) is one kind of commercial timber from dipterocarp family found in Sulawesi. This species is one of the types of plants that have the type of recalcitrant seeds. This study aims to determine the effectiveness of using growth retardants in the nursery.The experimental design used in this research is completely randomized design. The results showed the use of growth retardants provide excellent effectiveness in inhibiting the growth of seedling of S.assamica. Paklobutrazol of 250 ppm is a the best treatment that can provide growth inhibition. Percentage of growth inhibition of seedling age of 6 months amounted to 75,14 % (height) and 33,33% (diameter).